Bioflokulan Materials from Carrageenan and Agar on Seaweed Harvesting Process of Phytoplankton Dunaliella salina - Annur Ahadi Abdillah; Mochammad Amin Alamsjah; M. Nur Ghoyatul Amin (Journal of Aquaculture Science, 2018)
Harvesting microalgae is an important part in the culture system to produce higher crop biomass. Microalga Harvesting can be done by several techniques such as centrifugation, filtration, sedimentation, flocculation, ultrasonic vibration, and using filter. The technique currently used on an industrial scale is flocculation. This technique is used because it is more quickly and efficiently. Flocculants safe materials are polymers of polysaccharide seaweed. The study was conducted to determine the efficiency of the use of flocculants from alginate, carrageenan, so that the flocculation process microalgae Dunaliella salina. Flocculation process at the 50-minute show flocculation by material alginate by 30.52%, 22.85% by carrageenan, 11 % by Agar, plankton without flocculation make flocculates only amounted to 3.96%. Flocculation process at 240-minutes unchanged where carrageenan increased flocculation becomes 39.84%. Agar increased to 31, 48%. Plankton added flocculant alginate did not experience significant changes that just turned into 30.89%. The research results Show best flocculation activity is carrageenan where flocculation speed equal to alginate that has been frequently used as flocculants.Keyword : Dunaliella salina, flocculants, Carrageenan, Alginate, Agar